THE EFFECT OF SAMPLE TEMPERATURE VARIATIONS ON MEASURED URINE ALCOHOL CONCENTRATION: A SYSTEMATIC REVIEW - Kurniawan, Salsabila Yunita (Meditory : The Journal of Medical Laboratory, 2024)
Background: If an alcohol-containing urine sample cannot be analyzed immediately or requires shipping, it should be stored at an appropriate temperature. Pre-analytic is a stage that needs serious attention where at this stage the risk of errors often occurs. Error in storage samples can affect the results of alcohol concentration, so a laboratory technician needs to understand urine sample storage to measure alcohol concentration. Aims: Knowing the best storage of urine temperature in measuring alcohol concentration. Methods: This study used a systematic literature review of urine samples to measure alcohol concentration. The results: The storage temperature on measured urine alcohol concentration was carried out from 1977 – 2023. It can be seen that in some studies regarding storage temperatures in urine using at least 5 temperatures: -20oC, 4oC, 6oC, 14oC, ±20oC. The temperature storage at 4oC can prevent the production of ethanol due to microorganism activity, it will maintain the stability of alcohol concentration in urine. Conclusions: A temperature of 4oC is highly recommended for measuring alcohol concentration in urine samples.